2011
DOI: 10.1038/nphys2034
|View full text |Cite
|
Sign up to set email alerts
|

Aharonov–Bohm interferences from local deformations in graphene

Abstract: One of the most interesting aspects of graphene is the tied relation between structural and electronic properties. The observation of ripples in the graphene samples both free standing and on a substrate has given rise to a very active investigation around the membrane-like properties of graphene and the origin of the ripples remains as one of the most interesting open problems in the system. The interplay of structural and electronic properties is successfully described by the modelling of curvature and elast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
149
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(151 citation statements)
references
References 48 publications
1
149
0
1
Order By: Relevance
“…where g α (ξ 1 , ξ 2 ) is a tangent vector field, δ αβ is the reference (flat) metric andn = g ξ 1 ×g ξ 2 |g ξ 1 ×g ξ 2 | is the local normal [13,23,26,32,33]. However, peculiarities of how graphene ripples [38,39,40,41,42], slides and adheres [39,43] may be beyond first-order continuum elasticity.…”
Section: The Discrete Geometry Of Two-dimensional Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…where g α (ξ 1 , ξ 2 ) is a tangent vector field, δ αβ is the reference (flat) metric andn = g ξ 1 ×g ξ 2 |g ξ 1 ×g ξ 2 | is the local normal [13,23,26,32,33]. However, peculiarities of how graphene ripples [38,39,40,41,42], slides and adheres [39,43] may be beyond first-order continuum elasticity.…”
Section: The Discrete Geometry Of Two-dimensional Materialsmentioning
confidence: 99%
“…α pyr is a signed quantity, as follows: Direct inspection of Eqn. (33) indicates that α pyr will be positive for a bulge, and negative for a sag. Similarly, the mean curvature H D -Eqn.…”
Section: Chemical Measures and Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of possible effects due to the pseudo magnetic fields associated with local deformations of the graphene is given in [18], where the authors propose a device to measure Aharonov-Bohm interferences at the nanometre scale. The interplay between the pseudo-magnetic field and an external real one has been addressed in [19], where it was shown that due to an inherent competition between the two fields, the electric current exhibited spatial inhomogeneity not present when the real magnetic field is zero.…”
Section: Introductionmentioning
confidence: 99%
“…Curvature in a geometrical approach can be translated into a pseudo magnetic field or, more generally, into pseudo gauge fields which can lead to observable phenomena; see e.g the references [2,16,17,18].…”
Section: Introductionmentioning
confidence: 99%